Smart Indoor Home Surveillance Monitoring System Using Raspberry Pi - Lee Han Keat; Chuah Chai Wen (JOIV : International Journal on Informatics Visualization, 2018)
Internet of Things (IoTs) are internet computing devices which are connected to everyday objects that can receive and transmit data intelligently. IoTs allow human to interact and control everyday objects wirelessly to provide more convenience in their lifestyle. The Raspberry Pi is a small, lightweight and cheap single board computer that can fit on human’s palm. Security plays a big role in a home. People concern about security by preventing any intruders to enter their home. This is to prevent loss of privacy and assets. The closed-circuit television (CCTV) is one of the device used to monitor the secured area for any intruders. The use of traditional CCTV to monitor the secured area have three limitations, which are requiring a huge volume of storage to store all the videos regardless there are intruders or not, does not notify the users immediately when there are motions detected, and users must always check the CCTV recorded videos regularly to identity any intruders. Therefore, a smart surveillance monitoring system is proposed to solve this problem by detecting intruders and capturing image of the intruder. Notifications will also be sent to the user immediately when motions are detected. This smart surveillance monitoring system only store the images of the intruders that triggered the motion sensor, making this system uses significantly less storage space. The proposed Raspberry Pi is connected with a passive infrared (PIR) motion sensor, a webcam and internet connection, the whole device can be configured to carry out the surveillance tasks. The objectives of this project are to design, implement and test the surveillance system using the Raspberry Pi. This proposed surveillance system provides the user with live stream of video feed for the user. Whenever a motion is detected by the PIR motion sensor, the web camera may capture an image of the intruder and alert the users (owners) through Short Message Service (SMS) and email notifications. The methodology used to develop this system is by using the object-oriented analysis and design (OOAD) model.